The Assessment of Asbestos Exposure Using Semi-Quantitative Approach and Its Impact on Indonesian Male-Workers’ Health - ., Handayani; Mansyur, M; Sulistomo, A W; Marojahan Mulia, R (KnE Life Sciences, 2019)
Although asbestos has stated as a carcinogen it is still used worldwide in some countries including Indonesia. Very few asbestos studies have been done in Indonesia which underlines the urgency of this study. This study aimed to measure the asbestos exposure among workers using semi-quantitative methods and analyze its impact on workers’ health. This study used a cross-sectional design conducted in a factory which manufactured asbestos-contain materials (ACM) in West Java. We measured asbestos ambient levels at 19 points of workplace unit area representatively. The personal dose was measured for 56 male-workers. These data analyzed by an environmental laboratory. The chest x-ray and spirometry tests were performed by a reputable laboratory. The asbestos ambient levels at 19 points ranged from 0.02 to 0.53 fiber/cc. 36.8% of these points were higher than asbestos threshold limit value (TLV) 0.1 fiber/cc. The personal asbestos doses among 56 respondents ranged from 0.09 to 1.32 fibers/cc, and 92.9% of workers had an exposure level which exceeded the TLV. The chest x-ray results were standard, while eight workers had restrictive spirometry test results. These workers were susceptible to developing asbestos-related diseases (ARDs) due to a high level of asbestos exposure. Even though the chest x-ray gave standard results currently, the spirometry results had indicated the decrease of pulmonary function among these workers. Keywords: Asbestos; worker; semi-quantitative; chest x-ray; spirometry